GAME SITUATION AS A MEANS OF FORMING COMMUNICATIVE COMPETENCES IN STUDENTS - Topcu, Iskender (Mountain School of Ukrainian Carpaty, 2018)
The article analyzes the role of gaming situations in the process of forming communicative competences in students. A traditional approach to learning is not always justifiable in a modern comprehensive school setting, as it does not adequately provide for intensive acquisition of knowledge. The use of the game situation system permits effective shaping, improving and developing the skills and abilities for all types of language activities. The game exercises, when used systematically, help to model the conditions of real communication in the learning process, which in turn leads to an increased level of motivation to learn a foreign language. The situation as a relationship system does not appear arbitrarily. Students can be provided with specific situational positions, so that the situation will arise and function on their basis, thus permitting to plan the necessary for controlled learning situations in advance. The situation is a universal form of the communication process functioning that exists as an integrative dynamic system of social status, role, activity and moral relationships between the subjects of communication, reflected in their minds and arising from the interaction of their situational positions. In the context of our study, we have defined game situations during foreign language lessons as an active type of educational activity aimed at simulation modeling the systems, processes, and phenomena being studied. Game exercises with an element of competition provide motivation for learning and speech activities due to participation in game activities. Game situations with a role-based component contribute to enhancing motivation of student participation in foreign language communication in the classroom and formation of students’ communication skills. The game situation is the set of tasks that include specially designed learning situations and communicative dialogues that contribute to the design of the process of development of the communicative potential of an individual student.